IMPLEMENTASI AJARAN TAMANSISWA TRI NGA PADA PEMBELAJARAN PENDIDIKAN JASMANI - Taryatman, Taryatman; Rahim, Abdul (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2020)
This study aims to describe the implementation of physical education learning can be seen from how the implementation of Tri Nga Tamansiswa teachings in physical education learning takes place during the learning process. The scope of the implementation of physical education learning is the planning, process, and assessment of learning outcomes. The research method used is descriptive qualitative using a survey approach. Data collection techniques in this study are direct observation techniques in the field during the physical education learning process, direct interview techniques for physical education teachers and students, and documentation techniques that collect various images or data that support this research. The instrument used in this study was an interview guide. Data collected through direct observation during physical education learning, direct interviews with physical education teachers and students as well as images and data collected through documentation in order to obtain an overview or conclusion regarding the implementation of Tri Nga Tamansiswa teachings in physical education learning at Taman Muda Elementary School Ibu Pawiyatan.